The Relationship Between Peer Social Support and Anxiety in Final Year Students Who Are Writing Their Thesis - Yani, Fifi Siti Fauziah; Nurmansyah, Andri; Bola, Ibrahim N.; Imelisa, Rahmi; Wisnusakti, Khrisna; Fazrianti, Rizma Piarsihan (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: The demands of completing a final project, coupled with an individual's lack of preparedness, can give rise to psychological problems such as anxiety, stress, and depression. Factors influencing anxiety include social support, trust, and modeling. Among these, peer social support plays a particularly significant role in the academic environment. Objective : This study aimed to examine the relationship between peer social support and anxiety among final-year students preparing their undergraduate thesis in the Nursing Study Program. Methods: This study employed a quantitative research design with a cross- sectional approach. A total of 110 final-year students were selected using stratified random sampling. Data were collected using standardized questionnaires: the Hamilton Rating Scale for Anxiety (HRS-A) to measure anxiety levels and the Peer Social Support Scale to assess peer social support. Data were analyzed using univariate and bivariate techniques, with the chi-square test applied to determine the relationship between variables. Results: The results of the study showed that out of 110 respondents, 10 (9.1%) had panic anxiety, 30 (27.3%) were severe, 20 (18.2%) were mild, and 24 (21.8%) had no anxiety. Peers were found to be 28 (25.5%) low, 53 (48.2%) moderate, and 29 (26.4%) high. The results of the relationship analysis obtained a P value of 0.0001 (α <0.05), which shows that there is a relationship between peer social support and anxiety. Conclusion: Based on the results of research and discussion regarding the Relationship between Peer Social Support and Anxiety in final-year students Who Are Writing Their Thesis in the Nursing Study Program (S-1), Faculty of Health Science and Technology, Jenderal Achmad Yani University